Care experienced information rights and organisational practice - Caroline Anderson (Scottish Journal of Residential Child Care)
This paper provides a commentary on how organisations can close the gap and build their capability to better meet the information rights of care experienced adults seeking access to records about their childhood in the care of the State. It provides an overview of requirements in respect of access to records by people with care experience, and of advocates who campaign for improvements to information rights. Looking beyond the legislative compliance aspects of how organisations meet those information rights, it highlights root cause issues in the broader holistic records access and information rights agenda. The paper discusses potential learning about care records from an organisational perspective, describing the complexities inherent with their identification, form, content and meaning. The paper concludes with possible solutions that could be applied to organisational practice today.